Analisis Finansial Sistem Agroforestri Di Desa Puundirangga Kecamatan Laonti Kabupaten Konawe Selatan - Mando, La Ode Agus Salim; Arafah, Nur; Kandari, Aminuddin Mane; Kasim, Safril; Ramadhani, Desyi (Universitas Pattimura, 2022)
Using a plot of land in community forests with a combination of various plants is expected to increase production and profits in a sustainable manner. Therefore, this study aims to determine agroforestry patterns and their financial feasibility in the community forest. This study used direct observation methods and interviews with the purposive sampling method considering ownership and types of plants in community forests using agroforestry systems. The results showed that the financial analysis of the three types of agroforestry was declared feasible for development. Financial analysis within 40 (forty) years using an interest rate of 6% obtained an A1 type agroforestry system obtaining an NPV of Rp. 583,969,740.21 and for a 9% interest rate of Rp. 177,426,885.94. Meanwhile, the results of the BCR (Net Benefit Cost Ratio) analysis obtained an A1 type agroforestry system at an interest rate of 6% of 15.20 and an interest rate of 9% of 12.23. Finally, the highest IRR (Internal Rate Of Return) results in type A1 were 8.30%, and types A2 and A3 were 7.95% and 8.11%, respectively.